Los procesos metodológicos que se utilizan en el bloque de juegos grandes (mini baloncesto) en las escuelas del cantón Sozoranga, provincia de Loja durante el año lectivo 2012 – 2013 - Núñez Valdivieso, José Manuel (2014)
This thesis is aimed at an analysis , study and aportaren improving the teaching of Physical Education of children / as through proper guidance to teachers. The research work was conducted in Canton Schools Sozoranga province of Loja , students of the fifth, sixth and seventh years of basic education , therefore it academically, socially and economically justified, because it is part of a research study and has a social purpose. The proposed objectives for this study were those that allowed direct and conduct research according to the needs of school Sozoranga Canton schools . The materials and methods used to successfully develop this work were: Scientific Method , Inductive, Deductive and Hypothetical - Description . The techniques applied : literature , observation, and surveys. Methods and techniques that allowed fulfill the proposed objectives and verifying and accepting the assumptions made . Applied according to surveys and data obtained it was determined that : 100% of the children surveyed like basketball , 71 % said that playing basketball is not adequate, 26% would help improve basketball practice , know the techniques and methods , 61 % more hours of Physical Culture . As surveys Teachers : Practice games applies : methodological processes 56%, 89 % rules . How is Basketball practice : 25 % good, 75 % regularly. What makes the practice of Basketball: 84 % lack of techniques and procedures , 69 % lack of sports equipment . Knowledge methodologies for teaching minibaloncesto : 64 % in part. With all these results could establish findings : Teachers who teach courses of Physical Culture , are not specialized in this field , and do not make schedules which aim to teach children about the basics of mini - basketball. The lack of knowledge that exists on the part of teachers, on the basics of mini - basketball, influences the planning, block games Area Physical Culture in the fifth , sixth and seventh years of Basic Education Schools Sozoranga canton . There is no structure or an educational planning based on block area games Physical Education for teaching the basics of mini - basketball. Practice ' mini - basketball in school children Canton Sozoranga , not done properly, due to the lack of specialist teachers in Physical Culture and the lack of tools and / or equipment required to work in this sport.